The quantum vacuum : an introduction to quantum electrodynamics - Milonni, Peter W. (Academic Press, 1994)
In modern physics, the classical vacuum of tranquil nothingness has been replaced by a quantum vacuum with fluctuations of measurable consequence. In The Quantum Vacuum, Peter Milonni describes the concept of the vacuum in quantum physics with an emphasis on quantum electrodynamics. He elucidates in depth and detail the role of the vacuum electromagnetic field in spontaneous emission, the Lamb shift, van der Waals, and Casimir forces, and a variety of other phenomena, some of which are of technological as well as purely scientific importance. This informative text also provides an introduction based on fundamental vacuum processes to the ideas of relativistic quantum electrodynamics and quantum field theory, including renormalization and Feynman diagrams. Experimental as well as theoreticalaspects of the quantum vacuum are described, and in most cases details of mathematical derivations are included. Chapter 1 of The Quantum Vacuum - published in advance in The American Journal of Physics (1991)-was later selected by readers as one of the Most Memorable papers ever published in the 60-year history of the journal. This chapter provides anexcellent beginning of the book, introducing a wealth of information of historical interest, the results of which are carefully woven into subsequent chapters to form a coherent whole.